T cell responses in repeated controlled human schistosome infection compared to natural exposure - Emmanuella Driciru; Jan Pieter R. Koopman; Sanne Steenbergen; Friederike Sonnet; Koen A. Stam; Laura de Bes-Roeleveld; Eva Iliopoulou; Jacqueline J. Janse; Jeroen Sijtsma; Irene Nambuya; Stan T. Hilt; Marion König; et al. (Nature Communications)
Abstract In Schistosoma-endemic regions a lack of natural sterilizing immunity means individuals are repeatedly infected, treated and reinfected. Due to difficulties in tracking natural infection, kinetics of host immune response during these reinfections have not been elucidated. Here, we use repeated (3x) controlled-human-Schistosoma mansoni infection (CHI) to study how antigen-specific T cells develop during reinfection (NCT05085470 study). We compared these responses to naturally infected endemic Ugandan individuals (HALLMARK study). A mixed Th1/Th2/regulatory CD4+ T cell response develops in repeated CHI. Adult-worm-specific responses after repeated CHI were similar to endemic-natural infection. However, endemic participants showed differential responses to egg- and cercariae-antigens. Repeated CHI with sequential exposure to cercariae of different sexes (male-female-male) revealed an elevated CD4+ T cell cytokine response to adult-worm and egg-antigens. Our findings demonstrate that single-sex schistosome infection elicits adult-worm-specific T cell cytokine responses that reflect endemic-natural infection. This study advances our understanding of the immunology of schistosome (re)infection in the human host.